Pengaruh Literasi Ekonomi dan Literasi Digital Terhadap Prestasi Belajar Pada Mata Pelajaran Ekonomi Siswa Kelas X-E3 SMA Negeri 3 Sidoarjo di Masa Pandemi Covid-19 - Aisyah, Sabrina; Dewi, Retno Mustika (Jurnal Pendidikan Ekonomi (JUPE), 2022)
This research is motivated by the phenomenon that occurs, the results show that students still have a low level of economic literacy and lack of understanding of digital literacy in X-E3 class students at SMAN 3 Sidoarjo. In the current pandemic era, it requires students to be able to understand economic literacy and digital literacy in order to support a learning process. The low learning achievement of class X-E3 students of SMAN 3 Sidoarjo is the reason for conducting a study. The purpose of this study is to find out 1) The influence of economic literacy on learning achievement, 2) The effect of digital literacy on student learning achievement, 3) The influence of economic literacy and digital literacy on learning achievement. The results of the study concluded that there was a significant effect between economic literacy on student achievement and did not have a significant influence between digital literacy on student achievement and there was a significant value between the variables of economic literacy and digital literacy on learning achievement so that it had a simultaneous or simultaneous effect. This study uses quantitative research by means of data collection techniques in the form of questionnaires and documentation. From the results of data collection, it will be processed using statistical analysis techniques using SPPS software. The solution given to this research is to learn more about economic literacy and science related to basic economic concepts and learn and understand digital literacy because it will be very important to use now and in the future.